Research Progress of Hair Cell Protection Mechanism - Yurong Mu; Hongguo Su; Fan Wu; Jianming Yang; Dan Li (Neural Plasticity)
How to prevent and treat hearing-related diseases through the protection of hair cells (HCs) is the focus in the field of hearing in recent years. Hearing loss caused by dysfunction or loss of HCs is the main cause of hearing diseases. Therefore, clarifying the related mechanisms of HC development, apoptosis, protection, and regeneration is the main goal of current hearing research. This review introduces the latest research on mechanism of HC protection and regeneration.